Clarifying what is a safe haven : an application to the Gold Market - Matos, Ana Maria Aires Correia de (2016)
In this thesis, a new approach to the notion of safe haven is developed, building on earlier innovative work by Paulos (2015), and departing from the widely used Baur and Lucey (2010) benchmark. It is our view that such a benchmark neglects the flight-to-quality property a safe haven asset should have. As such, we suggest implications for risk preferences in safe haven assets namely in their possible flight to quality property, we develop a method to test such preferences, and we conduct an extensive study, for a large class of assets, on whether or not gold could be perceived as a safe haven with respect to them. Gold was chosen for this application for the purposes of comparison with similar studies in the Baur and Lucey (2010) tradition. The role of volatility is extensively discussed, and explicitly incorporated in the definition of safe haven, shifting from the correlation between returns paradigm. Our analysis finds out that when the safe haven definition is extended in the ways we have suggested, gold is a safe haven against a wide variety of financial assets. This result differs from the existing literature, but makes perfect sense in our sample period (2008-2013), which comprises the financial crisis of 2007-08 and the European debt crisis. The debate between gold as a hedge and as a safe haven is also analysed. The prevailing dichotomy between such roles in the literature is broken, since our approach to safe haven uses volatility measures, whilst the previous paradigm was based on assets’ returns. As such, we find that there were subperiods where gold did perform the role of hedge, but we do not find a contradiction between that and the role of safe haven for the entire sample period.